Analyzing the Impact of Social Assistance Programs on Poverty Alleviation in Karo Regency - Simbolon, Roma Sinta (Law and Economics, 2022)
This research delves into an in-depth analysis of the impact of social assistance programs on poverty alleviation within Karo Regency. Employing a mixed-methods approach encompassing qualitative and quantitative methodologies, the study investigates the effectiveness and nuances of these initiatives in addressing multifaceted dimensions of poverty. The research reveals multifaceted insights, showcasing both successes and limitations of social assistance programs. While the initiatives demonstrated commendable improvements in household incomes, access to essential services, and socio-economic indicators, nuanced outcomes emerged, revealing disparities among demographic groups, unintended consequences like dependency on aid, and the interplay of cultural context in program effectiveness. Drawing implications from the findings, the research suggests targeted policy modifications, emphasizing inclusivity, sustainability, empowerment, and community engagement within social assistance programs. The study contributes valuable insights to the discourse on poverty alleviation, highlighting the need for a more nuanced and participatory approach to enhance the impact of social assistance initiatives in Karo Regency.